Human Resource Development to Improve Employee Performance at the Sulawesi One River Regional Center, North Sulawesi Province - Chelly Theresye Langi; Maria H. Pratiknjo; Burhan Niode (Syntax Idea)
This research aims to analyze human resource development to improve employee performance at the Sulawesi River One Regional Office, North Sulawesi Province. The research uses a research design with a qualitative descriptive approach. This research focuses on the stages of HR development as a strategy to improve employee performance based on indicators consisting of motivation, personality and with 12 informants. Data analysis is carried out in the stages of data reduction, data presentation and drawing conclusions or verification. The research results show that in the context of developing human resources to improve employee performance at BWS 1 North Sulawesi Province on motivation indicators, there are two forms of motivation, namely direct motivation and indirect motivation. Where direct motivation is in the form of praise, awards, bonuses and service stars. Meanwhile, indirect motivation involves providing job support facilities. Developing human resources from personality indicators, leaders build a sense of ownership of the work given, a "sense of belonging" and provide a form of cadre formation for subordinates by developing skills at work. Based on skill indicators, employees are given coaching and counseling that is oriented towards the ability to carry out work with quality results and leaders hone employees' abilities by providing work and individuals must be willing to develop themselves, including being able to take advantage of digital opportunities as part of self-investment and being able to set priorities well. The conclusion of this research is that human resource development for employees at BWS 1 North Sulawesi province has been carried out in order to improve employee performance both in terms of motivation, personality and skills